Global environmental concern: A cross-national, structural and multilevel model - Pisano Martínez, Ignacio (Universidad de Málaga, Servicio de Publicaciones, 2014)
Researchers have not developed an adequate understanding of the processes influencing the formation of environmental concern, the relative explanatory power of individual level and contextual-level factors, and the extent to which similarities or differences can be noted across countries to in this respect. In this dissertation we address these issues in a cross-national study that uncovers similarities and differences within and between countries in environmental concern and behavior.
Keywords: Medio ambiente - Protección - Tesis doctorales; Estudios transculturales - Tesis doctorales; Environmental concern; Pro-ecological behavior; Cross-cultural comparison; Multilevel analysis